The Emotional Repression in Jamie Miller’s Character in Netflix's Adolescence (2025) Through the Lens of Emotional Capitalism - Dhiyaun Najikhah; Ayu Saraswati (FKIP, Universitas Palangka Raya, 2026)
This study examines emotional repression in Jamie Miller's character in the Netflix miniseries Adolescence (2025) through Eva Illouz’s theory of emotional capitalism. Employing a qualitative, socio-cultural literary approach, this study analyzes selected scenes and dialogue to explore how emotional repression is represented and how family dynamics shape Jamie’s emotional regulation. The findings reveal three interconnected patterns: silence and withdrawal as conditioned emotional responses, misdirected aggression as a product of emotional dysregulation, and the intergenerational transmission of emotional repression through family emotional capitalism. Rather than a personal failing, Jamie’s emotional repression is understood as a structurally produced outcome of a social system that rewards emotional control and penalizes vulnerability. This study contributes to the growing body of research on emotional capitalism in adolescent media narratives. It contributes to the growing body of research on emotional capitalism, adolescent identity, family communication, and the representation of mental and emotional conflict in contemporary media narratives in global digital streaming culture today.